NICOTIANA TABACUM AS A POTENTIAL PLATFORM FOR THE PRODUCTION OF RECOMBINANT ANTI-TOXOPLASMA SINGLE-CHAIN FRAGMENT (scFv) ANTIBODY - Mohamad Zoolkefli, Fatin Iffah Rasyiqah; Go, Pei See; Tan, Boon Chin; Rejab, Nur Ardiyana; Othman, Rofina Yasmin; Khalid, Norzulaani (Malaysian Journal of Science, 2020)
Abstract Plant systems have now gained much attention as they provide low risk of pathogen contamination and cost of production, appropriate post-translational modification, and multimeric assembly capability compared to the mammalian and bacterial hosts. In this study, we aimed to produce single-chain fragment antibody (scFv) encoding anti-Toxoplasma proteins, TP60 in Nicotiana tabacum cv. SR1. Leaf explants of N. tabacum were infected with Agrobacterium tumefaciens strain LBA4404 harbouring binary vector pCAMBIA1304 containing TP60 gene. Putative transformants were confirmed through GUS and GFP qualitative assays. Bands observed at the predicted size of 914 bp confirmed the presence of TP60 transgene and the transgene was stably integrated in both T0 and T1 tobacco genome. FV12-6 transgenic line produced the highest mRNA expression (7-fold) correlated to the highest accumulation of anti-Toxoplasma recombinant scFv antibody (0.52 % of the total soluble protein), followed by FV16-10 (0.25 %), FV17-7 and FV3-11 (0.18 %). The expression of TP60 transgene did not affect the growth of the transgenic plants and the segregation analysis of FV3, FV12, and FV16 in T1 generation confirmed the transgene integration within a single locus according to 3:1 Mendelian’s law. These findings indicated the possibility of using plants as a bio-factory for recombinant protein production. Abstrak Sistem tumbuhan kini telah mendapat banyak perhatian kerana mereka menyediakan risiko yang rendah terhadap pencemaran patogen dan kos pengeluaran, pengubahsuaian pasca-protein translasi yang sesuai, dan keupayaan penggabungan multimerik berbanding dengan tentera mamalia dan bakteria. Dalam kajian ini, kami berhasrat untuk menghasilkan antibodi serasi rantaian tunggal (scFv) yang mengekodkan protein anti-Toxoplasma, TP60 di Nicotiana tabacum cv. SR1. Eksplan daun N. tabacum telah dijangkiti oleh Agrobacterium tumefaciens strain LBA4404 yang menyimpan vektor dedua pCAMBIA1304 yang mengandungi gen TP60. Transforman putative disahkan melalui ujian kualitatif GUS dan GFP. Band-band yang diperhatikan pada saiz ramalan 914 bp mengesahkan kehadiran TP60 transgen dan transgen tersebut telah diintegrasi secara stabil dalam genom tembakau T0 dan T1. Individu transgenik FV12-6 menghasilkan ekspresi mRNA tertinggi (7 kali ganda) berkait dengan pengumpulan tertinggi antibodi rekombinan scFv anti-Toxoplasma (0.52% daripada jumlah protein larut), diikuti oleh FV16-10 (0.25%), FV17-7 dan FV3-11 (0.18%). Ungkapan transgenik TP60 tidak menjejaskan pertumbuhan tumbuhan transgenik dan analisis pemisahan FV3, FV12, dan FV16 dalam generasi T1 mengesahkan integrasi transgene dalam satu lokus mengikut 3: 1 undang-undang Mendelian. Penemuan ini menunjukkan kemungkinan menggunakan tumbuhan sebagai kilang bio untuk pengeluaran protein rekombinan. Keywords Agrobacterium-mediated transformation, plant molecular farming, recombinant protein, single-chain fragment antibody (scFv), tobacco, toxoplasmosis